Evaluasi penerapan program keringanan pajak kendaraan bermotor pada UPTD SAMSAT Tomohon - Lumintang, Rovel Dave Ryvalle; Sabijono, Harijanto; Suwetja, I Gede (Riset Akuntansi dan Portofolio Investasi, 2024)
Motor vehicle tax is a type of regional tax with significant potential for increasing local revenue. However, it must be acknowledged that there are still many taxpayers who do not comply with paying taxes on time. To increase taxpayer awareness, the Regional Government has implemented a motor vehicle tax relief program through UPTD Samsat Tomohon. This research evaluates the effectiveness of implementing the motor vehicle tax relief program in increasing taxpayer awareness of paying taxes at UPTD Samsat Tomohon. The research uses a qualitative approach with a descriptive methodology. Data sources were obtained through interviews, documents, and observations. The results show that the tax relief program increases taxpayer awareness and regional tax revenues.